1999
DOI: 10.1029/1999jb900167
|View full text |Cite
|
Sign up to set email alerts
|

Formation of natural gas hydrates in marine sediments: 2. Thermodynamic calculations of stability conditions in porous sediments

Abstract: A thermodynamic model for hydrate formation is used to compute the solubility of methane in pore water in equilibrium with gaseous methane or methane hydrate or both. Free energy of water in the hydrate phase and of methane in gas bubbles are corrected to account for salt effects and capillary effects. Capillary effects increase the solubility of methane in fluid in equilibrium with either hydrate or gas. Natural sediments have a broad distribution of pore sizes, and the effective pore size for capillary effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
383
1
5

Year Published

2005
2005
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 313 publications
(394 citation statements)
references
References 54 publications
4
383
1
5
Order By: Relevance
“…Hyndman et al [15] concluded that in situ data favour a base of the hydrate stability field controlled by the pure methane/pure water phase boundary. However, other authors (e.g., [12,16]) have favoured the pure methane/seawater boundary, and this boundary better fits the data from recent Ocean Drilling Program (ODP) legs [12] (Fig. 4).…”
Section: Heat Flowsupporting
confidence: 52%
See 2 more Smart Citations
“…Hyndman et al [15] concluded that in situ data favour a base of the hydrate stability field controlled by the pure methane/pure water phase boundary. However, other authors (e.g., [12,16]) have favoured the pure methane/seawater boundary, and this boundary better fits the data from recent Ocean Drilling Program (ODP) legs [12] (Fig. 4).…”
Section: Heat Flowsupporting
confidence: 52%
“…Thin solid and dashed lines are empirical fits to these data [13]. Thick solid and dashed lines are phase boundaries predicted by the theoretical approach of Tohidi et al [14] Here seawater is approximated by 560 mMol NaCl solution, and the dashed curve shown, which is the one used in this study, matches closely the seawater curve of [16]. Arrows mark the range of inferred temperatures at the BSR in our study area.…”
Section: Heat Flowmentioning
confidence: 59%
See 1 more Smart Citation
“…The accumulation of hydrate within the HSZ is controlled by geologic factors [e.g., Bünz et al, 2003;Riedel et al, 2006], pore fluid dynamics [e.g., Gorman et al, 2002;Hornbach et al, 2004], methane saturation levels in pore fluids [Gering et al, 2000], and anaerobic oxidation of methane [Borowski et al, 1996;Xu and Ruppel, 1999]. Additionally, the extent of the HSZ itself will be affected by such factors as pore water salinity and the composition of the gas (assumed in our case to be methane but possibly consisting of other natural gases) Henry et al, 1999]. It follows that the occurrence and concentration of hydrates within the HSZ are likely to be irregular and variable.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, knowledge about the thermodynamic mechanism(s) of formation and dissociation of hydrates in porous media is significant for research on gas hydrate storage and exploitation [4]. Many researchers have done much work based on this knowledge [5][6][7][8] and many study results have presented the fundamental pressure/temperature conditions properties of hydrate formation and dissociation in media [9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%